Christian Magistrate and Territorial Church: Johannes Brenz and the German Reformation. By James M. Estes - Matheson, Peter (The journal of theological studies, 2008)
Johannes Brenz (1499–1570) is hardly the most exciting of the Reformers, but in this substantial augmentation and revision of a 1982 monograph he emerges as a fine case study of ‘how the Reformation actually happened’ (p. 15). Throughout a long life his perseverance, integrity, and cooperative skills with colleagues and magisterial authorities gradually brought his utopian hopes closer to realization., Born into the governing urban élite, Brenz was initially influenced by humanism, establishing a sound linguistic base in Latin, Greek, and Hebrew for the flow of commentaries and catechisms which were later to find European-wide resonance.